Revisiting the SEMP Curriculum - Worrell, Patricia (Daily Express, 2004)
This article reflects on the author's hopes and expectations for the new phase of curriculum reform in the Secondary Education Modernisation Programme (SEMP) in Trinidad and Tobago
Keywords: Secondary school curriculum; Curriculum reform; Secondary Education Modernization Programme; Trinidad and Tobago